The PI3K/Akt Pathway in Tumors of Endocrine Tissues - Robbins, Helen Louise; Hague, Angela (Frontiers in Endocrinology, 2016)
The phosphatidylinositol 3-kinase (PI3K)/Akt pathway is a key driver in carcinogenesis. Defects in this pathway in human cancer syndromes such as Cowden’s disease and Multiple Endocrine Neoplasia result in tumors of endocrine tissues, highlighting its importance in these cancer types. This review explores the growing evidence from multiple animal and in vitro models and from analysis of human tumors for the involvement of this pathway in the following: thyroid carcinoma subtypes, parathyroid carcinoma, pituitary tumors, adrenocortical carcinoma, phaeochromocytoma, neuroblastoma, and gastroenteropancreatic neuroendocrine tumors. Whilst data are not always consistent, immunohistochemistry performed on human tumor tissue has been used alongside other techniques to demonstrate Akt overactivation. We review active Akt as a potential prognostic marker and the PI3K pathway as a therapeutic target in endocrine neoplasia.